2004
DOI: 10.1111/j.0301-5661.2004.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Demographic factors, denture status and oral health‐related quality of life

Abstract: Denture status was a stronger predictor for impaired OHRQoL than demographic variables and rendered age and education almost negligible in their influence on OHRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
175
5
14

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(216 citation statements)
references
References 20 publications
22
175
5
14
Order By: Relevance
“…Constatou-se uma melhor percepção de saúde bucal entre os indivíduos com maior escolaridade e com maior renda, no entanto a escolaridade não mostrou significância estatística na análise multivariada. Vários autores 11,14,19,26,27 encontraram uma percepção mais positiva da saúde bucal em indivídu-os com mais anos de estudo. Maupomé et al 28 , em uma pesquisa sobre percepção e satisfação com a saúde bucal, utilizaram o nível educacional como uma medida proxy da condição socioeconômica, entretanto não encontraram significância estatística; os autores sugeriram que tal resultado poderia ser explicado pelo fato de a amostra ser mais homogênea, composta somente por pessoas empregadas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Constatou-se uma melhor percepção de saúde bucal entre os indivíduos com maior escolaridade e com maior renda, no entanto a escolaridade não mostrou significância estatística na análise multivariada. Vários autores 11,14,19,26,27 encontraram uma percepção mais positiva da saúde bucal em indivídu-os com mais anos de estudo. Maupomé et al 28 , em uma pesquisa sobre percepção e satisfação com a saúde bucal, utilizaram o nível educacional como uma medida proxy da condição socioeconômica, entretanto não encontraram significância estatística; os autores sugeriram que tal resultado poderia ser explicado pelo fato de a amostra ser mais homogênea, composta somente por pessoas empregadas.…”
Section: Discussionunclassified
“…A baixa escolaridade e a privação material, dentre outros, podem ser importantes fatores determinantes de uma pior percepção da saúde 11,12 . Da mesma forma, pesquisas têm evidenciado associações entre condição de saúde bucal, autoavaliação de saúde bucal, consciência dos sintomas, características sociodemográficas, comportamentos relacionados à saúde bucal e qualidade de vida 13,14 .…”
Section: Introductionunclassified
“…Oral health-related QoL is affected by several factors such as age, gender, socio-economic status and tooth loss [25]. The relationships between socio-demographic factors, dental status and oral health related QoL were investigated in previous studies [24,26].…”
Section: Discussionmentioning
confidence: 99%
“…A national population-based study in Germany of adults 16-79 years of age showed that wearing a denture is a stronger factor for impaired OHRQoL than demographic variables (i.e. age, gender, education, years of schooling, and residential status) [34] while studies with participants between 20 and 70 years of age, found that the significance of tooth loss was ranked as being equal to the dissolution of marriage, retirement and problems with other relatives [35,36]. Missing natural teeth may lead to lower self-esteem, lower social status, and impaired function and decreased QoL, as underscored by Saintrain and de Souza [7], and can be an explanation for our findings.…”
Section: Quality Of Lifementioning
confidence: 99%